A maturidade em gerenciamento de projetos logísticos: o caso América Latina Logística - Noro, Greice de Bem (2006)
The technological innovation has resulted extraordinary advances to the human life, new expectations, leadership styles developments and ways to reach previously unattachable objectives. One of the consequences of this process is a large increase of resources for the project method and of the number and diversity of new projects and concepts. The projects management has gotten highligth into the administration models and has been the factor to provide speed, robustness, consistency and operational excellency in the achievement of projects. Also, models of maturity in projects management comes getting notoriety and at the same each time efforts to develop organizacionais abilities in the projects management are being doing. In this context, the present research had as objective the of the maturity level evaluation an organization of the national logistic sector. Describing the methodological procedures, the research is classified as quali-quantitative, descriptive, carried through a case study. This method was used to search informations about the company object of this study that had assisted the analysis of the quantitative information, obtained through the application of two models of evaluation of the maturity in projects management: the MMGP - Model of Maturity in Project Management - Sectorial - the Prado (2002) and PMMM - Project Management Maturity Model - 2 Level - Kerzner (2001). Through the combination of qualitative and quantitative methods, it was possible to indicate the level of company maturity, as well as the abilities necessary and possessed to reach the maturity in projects management.